2021
DOI: 10.3390/atmos12081009
|View full text |Cite
|
Sign up to set email alerts
|

Ambient PM2.5 and Daily Hospital Admissions for Acute Respiratory Infections: Effect Modification by Weight Status of Child

Abstract: The high level of ambient particulate matter in many developing countries constitutes a major health burden, but evidence on its impact on children’s health is still limited in these regions. We conducted a time-stratified case-crossover analysis to quantify the short-term association between fine particulate matter (PM2.5) and hospital admissions due to acute respiratory infections (ARI) among children in Bhaktapur district, Nepal, and to investigate the potential modification of the effect by nutritional cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…In another study, Linares and Díaz (2009) explain, for example, the association found between PM 2.5 and children's hospital admissions to the emergency room, compared to what had been detected with other pollutants. Similar evidence is also found in Bell et al (2015), Patto et al (2016), Nishikawa et al (2021), andRen et al (2021) among many others.…”
Section: A Review Of the Literaturesupporting
confidence: 89%
“…In another study, Linares and Díaz (2009) explain, for example, the association found between PM 2.5 and children's hospital admissions to the emergency room, compared to what had been detected with other pollutants. Similar evidence is also found in Bell et al (2015), Patto et al (2016), Nishikawa et al (2021), andRen et al (2021) among many others.…”
Section: A Review Of the Literaturesupporting
confidence: 89%